alpha-Calcium Calmodulin Kinase II Modulates the Temporal Structure of Hippocampal Bursting Patterns - Cho, Jeiwon; Bhatt, Rushi; Elgersma, Ype; Silva, Alcino J. (PUBLIC LIBRARY SCIENCE, 2012)
The alpha calcium calmodulin kinase II (alpha-CaMKII) is known to play a key role in CA1/CA3 synaptic plasticity, hippocampal place cell stability and spatial learning. Additionally, there is evidence from hippocampal electrophysiological slice studies that this kinase has a role in regulating ion channels that control neuronal excitability. Here, we report in vivo single unit studies, with alpha-CaMKII mutant mice, in which threonine 305 was replaced with an aspartate (alpha-CaMKIIT305D mutants), that indicate that this kinase modulates spike patterns in hippocampal pyramidal neurons. Previous studies showed that alpha-CaMKIIT305D mutants have abnormalities in both hippocampal LTP and hippocampal-dependent learning. We found that besides decreased place cell stability, which could be caused by their LTP impairments, the hippocampal CA1 spike patterns of alpha-CaMKIIT305D mutants were profoundly abnormal. Although overall firing rate, and overall burst frequency were not significantly altered in these mutants, inter-burst intervals, mean number of intra-burst spikes, ratio of intra-burst spikes to total spikes, and mean intra-burst intervals were significantly altered. In particular, the intra burst intervals of place cells in alpha-CaMKIIT305D mutants showed higher variability than controls. These results provide in vivo evidence that besides its well-known function in synaptic plasticity, alpha-CaMKII, and in particular its inhibitory phosphorylation at threonine 305, also have a role in shaping the temporal structure of hippocampal burst patterns. These results suggest that some of the molecular processes involved in acquiring information may also shape the patterns used to encode this information.
Keywords: COMPLEX-SPIKE CELLS; PLACE CELLS; SPATIAL MEMORY; SYNAPTIC PLASTICITY; FIRING PATTERNS; UNIT-ACTIVITY; RAT-BRAIN; NEURONS; CAMKII; MICE